Penurunan jumlah Streptococcus mutans pada saliva anak dengan ortodonti cekat setelah konsumsi yoghurt (Reduction of salivary Mutans Streptococci in children with fixed orthodontic appliance after yoghurt consumption) - Dewi Anggreani Bibi; Udijanto Tedjosasongko; Irmawati Irmawati (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Orthodontic treatment using fixed appliances in children increases with the case of malocclusion in Indonesia. The patients with fixed orthodontics have higher risks of caries. Purpose: The study was aimed to examine the influences short term daily consumption fruit-flavored yoghurt on salivary mutans Streptococci in pediatric patients during orthodontic treatment with fixed appliances. Methods: This was an experimental laboratory study with a double-blind randomized crossover design. The subjects were 26 children in range of age 11 to 15 years old who were under orthodontic treatment using fixed appliances. Subjects were divided into 2 (two) groups which consist of 13 children each. Group A were asked to consumed a 150 ml of yoghurt Bifidobacterium bifidum and Lactobacillus acidophilus once a day for 2 weeks, while group B were asked to consumed milk once a day for the same period of time. After “washout” period for 2 weeks, the subjects of group A and B crossed over the drink, group A was asked to consumed milk and group B was asked to consumed yoghurt for another 2 weeks. Before and after consuming yoghurt or milk, the subject’s saliva samples were taken and the colonies of mutans Streptococci were counted on TYC media. Results: Statistical analysis showed that on subjects who consumed yoghurt the colony number of mutans Streptococci reduced significantly (p < 0.05). Conclusion: Short-term daily consumption of the probiotic yoghurt containing Bifidobacterium bifidum bacteria and Lactobacillus acidophilus could reduce the number of salivary mutans streptococci in pediatric patient during orthodontic treatment with fixed appliances.Latar belakang: Kebutuhan perawatan ortodonti menggunakan alat cekat pada anak-anak meningkat seiring bertambahnya jumlah kasus maloklusi di Indonesia. Namun faktanya penggunaan piranti ortodonti cekat berisiko terjadinya karies disekitar bracket. Tujuan: Penelitian ini bertujuan meneliti pengaruh konsumsi yoghurt buah dalam jangka pendek terhadap jumlah Streptococcus mutans pada saliva anak pemakai ortodonti cekat. Metode: Jenis penelitian ini eksperimental laboratoris dengan desain penelitian double blind randomized crossover design. subjek penelitian adalah 26 anak berusia 11-15 tahun yang sedang menjalani perawatan ortodonti dengan piranti cekat. subjek dibagi dalam 2 kelompok dengan masing-masing 13 anak. Kelompok A diminta untuk mengkonsumsi 150 ml yoghurt Bifidobacterium bifidum dan Lactobachillus acidophillus sekali sehari selama 2 minggu, sedang kelompok B diminta untuk mengkonsumsi susu sekali sehari selama 2 minggu. Setelah periode “washout” selama 2 minggu, kedua kelompok bertukar minuman, kelompok A mengkonsumsi susu sedang kelompok B mengkonsumsi yoghurt selama 2 minggu. Setiap sebelum dan sesudah mengkonsumsi yoghurt dan susu, sampel saliva subjek diambil dan dilakukan penghitungan jumlah koloni Streptococcus mutans pada media TYC. Hasil: Analisa statistik menunjukkan bahwa setelah mengkonsumsi yoghurt jumlah koloni Streptococcus mutans dalam saliva subjek berkurang secara signifikan (p < 0,05). Simpulan: Konsumsi probiotik yoghurt yang mengandung Bifidobacterium bifidum dan Lactobachillus acidophillus dapat mengurangi jumlah koloni Streptococcus mutans dalam saliva anak selama perawatan ortodontik cekat.